Skill wage premia, employment, and cohort effects: are workers in Germany all of the same type? - Bernd Fitzenberger; Karsten Kohn (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2006)
This paper studies the relationship between employment and wage structures in West Germany based on the IAB employment subsample 19751997. It extends the analytical framework of Card and Lemieux (2001) which simultaneously includes skill and age as important dimensions of heterogeneity. After having identified cohort effects in skill wage premia and in the evolution of relative employment measures, we estimate elasticities of substitution between employees in three different skill groups and between those of different age, taking account of the endogeneity of wages and employment. Compared to estimates in the related literature, we find a rather high degree of substitutability. Drawing on the estimated parameters, we simulate the magnitude of wage changes within the respective skill groups that would have been necessary to halve skill-specific unemployment rates in 1997. The required nominal wage reductions range from 8.8 to 12.2% and are the higher the lower the employees' skill level.
Keywords: E24; J31; J21; 330; Labor Demand; Heterogeneity; Age; Skill; Wage Structure; Employment; Cohort Effects; Unemployment